2014
DOI: 10.1007/s00284-014-0709-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Composition of Three Candidate Insect Vectors of Palm Phytoplasma (Texas Phoenix Palm Decline and Lethal Yellowing)

Abstract: Texas Phoenix Palm Decline (TPPD) and Lethal Yellowing are two phytoplasma-linked diseases in palms. The phytoplasma causing TPPD is thought to be transmitted by three putative planthopper vectors, Ormenaria rufifascia, Omolicna joi, and Haplaxius crudus. These insects have been morphologically and molecularly described, and have screened positive for Candidatus Phytoplasma palmae. Individuals from each species were subjected to 16S bacterial community sequencing using the Roche 454 platform, providing new inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Even though the microbial communities of many phytoplasma vectors have been previously described (Marzorati et al 2006;Gonella et al 2011;Wangkeeree et al 2011Wangkeeree et al , 2012Iasur-Kruh et al 2013;Ishii et al 2013;Powell et al 2015), little information on the influence of the symbiotic microbiome on competence of the leafhopper vector of phytoplasmas is currently available (Trivedi et al 2016) despite the relevance to worldwide agriculture of these pathogens. Interactions between symbiotic bacteria and phytoplasma inside the insects have been proposed (Ishii et al 2013) but not yet demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the microbial communities of many phytoplasma vectors have been previously described (Marzorati et al 2006;Gonella et al 2011;Wangkeeree et al 2011Wangkeeree et al , 2012Iasur-Kruh et al 2013;Ishii et al 2013;Powell et al 2015), little information on the influence of the symbiotic microbiome on competence of the leafhopper vector of phytoplasmas is currently available (Trivedi et al 2016) despite the relevance to worldwide agriculture of these pathogens. Interactions between symbiotic bacteria and phytoplasma inside the insects have been proposed (Ishii et al 2013) but not yet demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…There has been no unequivocal evidence that derbids transmit palm pathogens, which remains a critical issue. Powell et al ( 2015 ) documented the presence of the 16SrIV-D phytoplasma in the newly discovered Omolicna joi ; however, this was based on DNA extraction from the whole body of the insect. Detection of phytoplasma from whole-body extractions of insects has some use in vector studies because it allows for the identification of species that are in fact feeding on infected palms.…”
Section: Discussionmentioning
confidence: 99%
“…It is the primary vector of Flavescence dorée phytoplasma (FDp), a quarantine pest currently present in the main grape-growing European countries (EFSA Panel on Plant Health et al, 2016 ). Most of the knowledge about the microbiome associated with S. titanus and other phytoplasma vectors is currently based on laboratory-reared insects and focuses almost exclusively on a few bacterial components (Campbell and Purcell, 1993 ; Marzorati et al, 2006 ; Sacchi et al, 2008 ; Gonella et al, 2011 ; Wangkeeree et al, 2012 ; Ishii et al, 2013 ; Powell et al, 2015 ; Iasur-Kruh et al, 2018 ). Only recently, a 16S metabarcoding analysis was conducted to provide a broader view of the bacterial microorganisms associated with “ Candidatus Phytoplasma solani” infected and non-infected insects caught in nature (Moussa et al, 2020 ), but such an approach neglects the other components of the microbiome that might be associated with the phytoplasma insect vectors (e.g., protozoa, fungi, and viruses).…”
Section: Introductionmentioning
confidence: 99%